Ground motion amplification at flange level of bushings mounted on electric substation transformers. - Villaverde, Roberto
A study was conducted to quantify the ground motion amplification that takes place at the base of bushings mounted on electric substation transformers as a result of the flexibility of the transformer tank and turrets to which they are connected. This study was undertaken to assess the adequacy of the amplification factor of 2.0 specified by the Institute of Electrical and Electronic Engineers in Standard IEEE 693-1997 for the seismic qualification of transformer bushings. The study included field tests of typical 500 kV transformers to obtain experimentally their natural frequencies and damping ratios, the development of simple analytical models that closely matched the experimental data, and the calculation of the transformers' dynamic response under different earthquake excitations using these analytical models. Amplification factors were then computed for each of the excitations considered, defining these amplification factors as the peak shear force at the base of the bushings over the corresponding shear force obtained when the bushings are assumed mounted directly on the ground. It is found that the amplification factors for the 500 kV bushings are within the amplification factor of 2.0 specified by Standard IEEE 693, but not those for the 230 kV bushings, which exceed the IEEE 693 amplification factor by almost a factor of two.
Keywords: Substation equipment; Seismic qualification; Field tests; Seismic response analysis; Equipment modeling; Experimental dynamic properties